2010
DOI: 10.5144/0256-4947.59374
|View full text |Cite
|
Sign up to set email alerts
|

Trauma care systems in Saudi Arabia: an agenda for action

Abstract: Saudi Arabia is undergoing a rapid population growth that along with improved socioeconomics has led many individuals to own a car or even a number of cars per family, resulting in a greater number of vehicles on the roads. The reduced focus on good public transportation systems and the dependence on cars for transportation have created a diversity of drivers who are unfamiliar with the local driving rules and lack the basic skills for safe driving. This is in addition to some young drivers who frequently viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…[5,9] In 2005, data obtained from traffi c sources of Saudi Arabia revealed that there were 283 684 RTAs, during which 5 883 people died. [10] Domestic accidents are worldwide public health problems. In some European countries, accidents at home kill more people than road accidents, in spite of strict safety regulations and laws regarding buildings and living areas.…”
Section: Introductionmentioning
confidence: 99%
“…[5,9] In 2005, data obtained from traffi c sources of Saudi Arabia revealed that there were 283 684 RTAs, during which 5 883 people died. [10] Domestic accidents are worldwide public health problems. In some European countries, accidents at home kill more people than road accidents, in spite of strict safety regulations and laws regarding buildings and living areas.…”
Section: Introductionmentioning
confidence: 99%
“…[5] According to world report on road traffic injury prevention, about 3000 people worldwide die every day from road traffic injuries. [9] Head and facial injuries account for 30% of all injuries and cause 26% of deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them are in the age group of 1-25 years. [1,5,20,21,22,23,24] Reasons for higher incidence in this age group have been cited earlier in this review which includes road rage, jumping signals, over confidence, use of mobile phones while driving. Most of the literature concludes with the fact that the incidence of road traffic accidents is comparatively more in males than in females.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies conducted in Arab countries on the incidence of road traffic accidents suggest speed, violence of traffic laws as the major factor. [1,2,5,7,13,18,20,22] Since alcohol is strictly prohibited by law in Islamic countries, role of drunken driving is negligible or insignificant. Irrespective of the etiological factor, most of the road traffic accidents occur in younger age group.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation